2010
DOI: 10.1097/pep.0b013e3181cd18a7
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Children with Cerebral Palsy: Implications for Pediatric Physical Therapy

Abstract: Research completed primarily by non-physical therapist healthcare professionals delineate assessment tools and psychosocial pain management techniques that hold promise for evaluating and reducing pain that occurs during PT procedures for children with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
0
15
0
2
Order By: Relevance
“…7 Standardized pain assessment tools were classified into self-report, physiological, behavioral, and composite measures. 7 Standardized pain assessment tools were classified into self-report, physiological, behavioral, and composite measures.…”
Section: Survey Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Standardized pain assessment tools were classified into self-report, physiological, behavioral, and composite measures. 7 Standardized pain assessment tools were classified into self-report, physiological, behavioral, and composite measures.…”
Section: Survey Developmentmentioning
confidence: 99%
“…[1][2][3] Families of children with CP identify bodily pain and pain associated with physical therapy as deterrents to high quality of life. 7 Specific features for pain measurement tools requiring consideration include psychometric properties, intended population, availability, and ease of administration. 7 Specific features for pain measurement tools requiring consideration include psychometric properties, intended population, availability, and ease of administration.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, when they attempted to identify which factors influenced worse QOL outcomes, they found that children with worse motor impairment obtained a low level of physical well-being, and that the presence of ID was related to poorer scores in mood and autonomy . It seems confirmed that the presence of pain has an impact on QOL, not only on the physical domains, but also on the emotional and social domains Dickinson et al 2007;Riquelme et al 2011;Swiggum et al 2010). Finally, according to Majnemer et al (2007), children with behavior problems may have more difficulties adapting to daily tasks and integrating socially, and this can affect their emotional well-being and relations with their classmates.…”
Section: Comorbidities and Quality Of Lifementioning
confidence: 87%
“…In contrast, according to Vargus- Adams and Martin (2011) pain was revealed to be one of the main treatment goals for health professionals who work with people with CP. From this perspective, Swiggum et al (2010) stated that 80 % of the physiotherapists attending children with neurological problems apply subjective measures to rate pain. Of them, 70 % use scales completed by the child, and 48 % use behavioral and physiological measures.…”
Section: Pain Managementmentioning
confidence: 99%
“…In attempts to correct and rehabilitate orthopedic problems, such as hip dislocations, children with CP often undergo surgical and medical procedures and interventions that may alleviate frequent pain in the long run (Engel & Kartin, 2006;Ramstad, Jahnsen, Skjeldal, & Diseth, 2011). However, painful experiences may arise during procedures such as needle injections, range of motion/movement manipulation, and assisted stretching (Swiggum, Hamilton, Gleeson, & Roddey, 2010). In conjunction with such procedures, professionals have an essential role in pain management (Bice, Gunther, & Wyatt, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%